2012
DOI: 10.1021/ol3030154
|View full text |Cite
|
Sign up to set email alerts
|

Alkene Dihydroxylation with Malonoyl Peroxides: Catalysis Using Fluorinated Alcohols

Abstract: The effect of fluorinated alcohols on the dihydroxylation of alkenes using cyclopropyl malonoyl peroxide is described. Addition of perfluoro-tert-butyl alcohol to a toluene solution of alkene and peroxide increases the rate of product formation and the stereoselectivity observed, providing a simple and effective method for acceleration of this important class of reaction. Basic hydrolysis of the crude reaction mixture provides access to syn-diols in high yield and stereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…This mechanistic pathway is consistent with previous investigations of the reactivity of the malonyl peroxides 4 . Based on the obtained results we can consider the discovered oxidative C−O coupling of malonyl peroxides with enol ethers as oxidative [5+2] cycloaddition from the formal point of view.…”
Section: Resultssupporting
confidence: 92%
“…This mechanistic pathway is consistent with previous investigations of the reactivity of the malonyl peroxides 4 . Based on the obtained results we can consider the discovered oxidative C−O coupling of malonyl peroxides with enol ethers as oxidative [5+2] cycloaddition from the formal point of view.…”
Section: Resultssupporting
confidence: 92%
“…FTIR (KBr): 3472, 2923, 1941, 1628, 1364 cm –1 . Analytical data are in accordance with literature data …”
Section: Experimental Sectionsupporting
confidence: 85%
“…Interestingly, it has been shown that fluorinated alcohols can be used to accelerate reactions involving peroxides. 50,51 It has also been shown that fluorinated alcohols have the ability to activate hydrogen peroxide, 52 which has been specifically exploited in oxidation reactions. Examination of hexafluoroisopropanol (HFIP) as an alternative reaction solvent resulted in an equivalent conversion of cyclohexanone 4 to the ester 5 (42%; entry 12).…”
Section: Optimization Of the Baeyer-villiger Reactionmentioning
confidence: 99%